English Teachersâ Perception on Educational Supervision - Praditya, Dion Wildan; Asib, Abdul; Rochsantiningsih, Dewi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The objective of this study was to describe the English teachersâ perception on educational supervision. This research was a qualitative study using purposive sample. The research was conducted in the three senior high schools which had different accreditation in Kalirejo, Lampung. The data were collected from the interview with three English teachers. Each of them represented different school. The data the researcher had included were all about how the English teachersâ perceptions on educational supervision in Kalirejo, Lampung. All the subjects in this research had been supervised before, thus they could describe their perceptions on educational supervision. The result of the research showed that the teachers believed that educational supervision is an ongoing process to observe the way teachers teach in the classroom according to the lesson plan and to improve their teaching skills.